Teachers' Perceptions of Parental Involvement in Primary Education - Valentina Lj. Gulevska (University of Belgrade, Teacher Education Faculty, 2018)
In this paper, we are taking an in-depth look at communicating with families of students in primary schools and there is a current research as the basis. Focusing on the partnership between teachers and parents, this research analyses different elements: communicating with families about the student's success, communicating with families in meetings, and addressing difficult topics with families. Additionally, a broad-based analysis is made regarding working with families of general education students, students with disabilities, students from low socio-economic status, and students with unique gifts and talents. Sometimes teachers working with families may become frustrated by the parents' apparent inability to dedicate their attention fully on matters regarding their children. At that point, there is a tendency of determination of teachers' perceptions of both the benefits of creating productive partnerships with parents, on one side and the barriers that must be overcome, on the other side.